Edaphic microbiota in plantain lots of contrasting vigor, and relationships with soil properties (Bioagro, 2021)
Edaphic organisms are responsible for regulation of biological processes, including mineralization and biological repair of the soil. In order to quantify the microbiota of the soil cultivated with plantain cv Harton in the South Maracaibo Lake, seven production units with lots of high (HV) and low vigor (LV) plants were selected. The number of hands per bunch, circumference of the mother plant and height of the succession sucker in 20 plants of each plot were measured. Likewise, soil samples at 15 cm depth were taken to quantify UFC of fungi, bacteria and actinomycetes, as well as soil physical, chemical and biological properties. Variables such as bulk density, fine particles content, organic matter, microbial carbon and microbial coefficient came out to be favorable in lots of HV plants. In general, no statistical differences in UFC of fungi and bacteria were observed between vigor lots; however, there were differences between HV and LV lots for actinomycetes, which result important organisms to determine dynamics in the soil and favor vigor of plantain plants under the study conditions.
Keywords: Actinomycetes; Harton; microbial activity; microbiota; Musa AAB